Fulminant Type 1 Diabetes Mellitus Associated With Drug Hypersensitivity and Epstein–Barr Virus Infection: A Case Report - Chen, Xing-Yu; Wang, Cong; Chen, Shizhi; Tian, Mingyuan; Wang, Xin; Zhang, Lili (Frontiers in Pharmacology, 2022)
BACKGROUND Fulminant type 1 diabetes mellitus (FT1DM) is a new subtype of type 1 diabetes, first proposed by Japanese scholars in 2000. Herein, the functions of the islets are rapidly destroyed. Its pathogenesis is related to viral infection. Most people have been infected with Epstein–Barr virus (EBV), and many people have also suffered from drug hypersensitivity, however, few cases of FT1DM which were caused by both of the two conditions have been reported. Thus, below, we describe one such valuable case. CASE SUMMARY The plasma glucose levels of a 73‐year‐old man diagnosed with drug-induced dermatitis showed a sudden increase (42 mmol / L) during methylprednisolone therapy. The urine ketone test was positive. The glycated hemoglobin level was 7%, endogenous insulin secretion decreased significantly, and the islet-related autoantibodies were negative. The patient was diagnosed with FT1DM. The lymphocyte EBV-DNA showed high copies numbers. The general condition of the patient improved after symptomatic treatment with insulin. However, the systemic allergic reaction aggravated after the use of iodinated contrast agents, prednisone, and thymic pentapeptide. The re-test for EBV-DNA showed significantly high relative levels, thus indicating the presence of EBV infection. We think that drug hypersensitivity and EBV infection together led to FT1DM in this case. After an indication for multiple daily insulin therapy, the patient’s blood glucose was quickly controlled and he was discharged on the 38th-day post-admission. CONCLUSION FT1DM is a rare case, however, drug hypersensitivity and EBV infection are not rare in the population. This is a rare case of FT1DM caused by drug hypersensitivity reaction and EBV infection. Through this case report, we emphasize the importance of the relationship between drug hypersensitivity, EBV infection and FT1DM and vigilance for the occurrence of FT1DM among hypersensitive individuals in clinical practice.